A Note on Some Evidence on the Easterlin Hypothesis - Olneck, Michael R.; Wolfe, Barbara L. (Journal of Political Economy, 1978)
According to the Easterlin hypothesis, the positive relationship between income and fertility is dependent on relative income. The hypothesis presumes that aspirations are significantly determined by family background. If income is high relative to aspirations, individuals will tend to have more children. The definition of variables as sibling differences controls family background and yields a measure of relative income. Analyzing the Kalamazoo Brothers sample in this fashion produces no evidence in support of the hypothesis.